Pencegahan Kanker Payudara melalui Sadari dan Sadanis di Era Pandemi Covid-19 - Hayati, Nur; Wahyuni, Alfaina; Kusumawati, Wiwik (Universitas Muhammadiyah Semarang, 2023)
Breast cancer is a contributor to high mortality rates in women, with a mortality rate of 18% of women's deaths. Public awareness in recognizing and identifying cancer symptoms at an early stage is still low, making cancer in Indonesia more at an advanced stage. This community service activity aims to increase community knowledge and skills in preventing and detecting breast cancer early through counseling about breast cancer and breast self-examination (BSE). This partner is the activity of PKK cadres who contribute to the implementation of health education and health cadres in their area. Community service methods with breast cancer counseling and BSE training. In this activity, a clinical breast examination (SADANIS) was also carried out in the form of a breast ultrasound examination to detect any abnormalities in the breast by a Radiology specialist. The speaker delivered material on breast cancer prevention and participants were given a pocket book on breast cancer prevention. Prior to participating in the counseling, participants were tested for their knowledge of breast cancer prevention using a pretest. After getting the presentation of the material, a posttest was conducted. The results of the pre and post analysis showed an increase in participants' knowledge about breast cancer prevention. Community service with counseling, pocket books and health checks succeeded in increasing participants' knowledge about breast cancer prevention.Keywords: SADARI, SADANIS, breast cancer.